2020
DOI: 10.1371/journal.pbio.3000642
|View full text |Cite
|
Sign up to set email alerts
|

Eco-evolutionary significance of “loners”

Abstract: Loners-individuals out of sync with a coordinated majority-occur frequently in nature. Are loners incidental byproducts of large-scale coordination attempts, or are they part of a mosaic of life-history strategies? Here, we provide empirical evidence of naturally occurring heritable variation in loner behavior in the model social amoeba Dictyostelium discoideum. We propose that Dictyostelium loners-cells that do not join the multicellular life stagearise from a dynamic population-partitioning process, the resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 58 publications
6
39
0
Order By: Relevance
“…The potential relevance of non-aggregated cells has been supported by experimental observations both on lab and wild strains. Different studies reported that a sizeable fraction of cells is invariably found outside aggregates, and that these cells are able to start vegetative growth when nutrients become available (Dubravcic et al, 2014;Tarnita et al, 2015;Rossine et al, 2020). The partition of a population in loner and aggregated components was modelled as the consequence of a cell-level stochastic choice, where the genotype determines the probability of staying alone (Dubravcic et al, 2014;Tarnita et al, 2015;Martínez-García & Tarnita, 2016).…”
Section: Environmental Fluctuations and Bet-hedgingmentioning
confidence: 99%
See 3 more Smart Citations
“…The potential relevance of non-aggregated cells has been supported by experimental observations both on lab and wild strains. Different studies reported that a sizeable fraction of cells is invariably found outside aggregates, and that these cells are able to start vegetative growth when nutrients become available (Dubravcic et al, 2014;Tarnita et al, 2015;Rossine et al, 2020). The partition of a population in loner and aggregated components was modelled as the consequence of a cell-level stochastic choice, where the genotype determines the probability of staying alone (Dubravcic et al, 2014;Tarnita et al, 2015;Martínez-García & Tarnita, 2016).…”
Section: Environmental Fluctuations and Bet-hedgingmentioning
confidence: 99%
“…As discussed earlier in this section, a possible source of indirect effects on the proportion of spores produced by one strain in a chimera is the partition between aggregated and non-aggregated cells. When exploring the mechanistic bases of this partitioning, the probability of being a loner was found to depend, other than on the genotype, on cell density and environmental factors such as the hardness of the agar substrate (Rossine et al, 2020). Such dependence on both the biotic and abiotic context was explained by a mathematical model where the cell decision to aggregate is stochastic and conditional on a locally established quorum.…”
Section: Cell-level Response To Social Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Studying the balance between species competitive and dispersal abilities is fundamental to understanding the role of space in maintaining biodiversity [1][2][3][4][5][6]. Competition-dispersal (or competition-colonization) tradeoffs have primarily been invoked to explain the structure of plant communities [7][8][9][10], but have also been measured in virus [11], insects [12], bacteria [13,14], rotifers and protozoan [15], and slime molds [16][17][18][19] among other lineages. A key result is that species that are weaker competitors may persist in the community because their enhanced dispersal, either in distance or rate, allows them to colonize empty patches before the stronger competitor arrives [2].…”
Section: Introductionmentioning
confidence: 99%